FGFR3 Nuclear Translocation Contributes to Proliferative Potential and Poor Prognosis in Pancreatic Ductal Adenocarcinoma. Issue 5 (19th May 2022) - Zhou, Li; Lu, Jun; Liang, Zhi-Yong; Zhou, Wei-Xun; Jiang, Bo-Lun; Wang, Yi-Zhi; Liu, Cheng-Xi; Huang, Bo-Wen; You, Lei; Guo, Jun-Chao
Abstract : Objectives: Fibroblast growth factor receptor 3 (FGFR3) was revealed to have divergent, even opposite roles in different neoplasms. In pancreatic ductal adenocarcinoma (PDAC), its impact on biological behavior and prognosis was not well elucidated. Methods: Fibroblast growth factor receptor 3 was downregulated by RNA interference to explore its impact on cell proliferative proclivity in PDAC cells. Furthermore, tissue microarray-based immunohistochemistry for FGFR3 was performed in 326 patients with PDAC who underwent radical resection, and its clinicopathologic and prognostic implications were then evaluated. Results: First, successful FGFR3 knockdown remarkably decreased its expression, cell proliferation, and S-phase ratio in the cell cycle in 2 PDAC cell lines, BxPC-3 and AsPC-1. Meanwhile, alterations in p-Akt, cyclin D1, cyclin B1, and p21 were also observed. Subsequently, high nuclear FGFR3 expression, but not cytoplasmic, was significantly common in tumor tissues and positively associated with N stage and dismal overall survival in the entire cohort. In addition, nuclear FGFR3 expression was also prognostic in 10 of 14 subsets. Univariate and multivariate Cox regression analyses identified nuclear expression of FGFR3 as an independent prognosticator in the entire cohort. Conclusions: Our data showed that FGFR3 nuclear translocation contributes to cell proliferative potential and predicts poor long-term prognosis in PDAC after surgical resection.